The Adoption of Product-Service System Business Models: A Multiple Case Study - Camila Peripolli Sanfelice; Jordana Marques Kneipp; Greice Eccel Pontelli (Journal of Technology Management & Innovation)
This study aimed to analyze the adoption of product-service system (PSS) business models, focusing on adoption and perception aspects of PSS, as well as elements intrinsic to the design of the PSS business model itself. A qualitative method was employed through a multiple case study, utilizing semi-structured interviews and secondary data analysis. The findings suggest that companies embracing PSS share a common drive for innovation. Moreover, PSS is adopted and perceived as a means to meet customer needs and provide efficient, customized products. Furthermore, the value proposition of the PSS business model emphasizes sustainability. For managers, this study offers insights into the workings of PSS business models and suggests strategies for managing their key components effectively.